Frequency of Urinary Tract Infection (UTI) in Neonates Admitted with Indirect Hyperbilirubinemia - Syed Moeed Ahmed, Pir Jan, Saeed Zaman, Shams-Uddin Kakar, Sajid Ali Shah, Ammara Ayub, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of urinary tract infection (UTI) in neonates admitted with indirect hyperbilirubinemia. Study Design: A cross-sectional study. Place and Duration of the Study: Inpatient department of Pediatric Medicine, Bolan Medical College/Hospital Quetta from Jan 2019 to Dec 2020. Methodology: A total of 130 neonates of either gender (delivered at ≥ 32 weeks) admitted with primarily complaints of jaundice (with evidence of indirect hyperbilirubinemia) were included. Sex, age, weight and height of all neonates were noted. Serum bilirubin levels were asses and urine samples were also evaluated for the existence of urinary tract infection (UTI). Results: In a total of 130 neonates, 58 (44.6%) were males and 72 (55.4%) females. The UTI was found to be present in 41 (31.5%) neonates admitted with indirect hyperbilirubinemia. Among these 41 culture proven UTI cases, most common organism was E. coli found in 15 (36.6%) cases while Klebsiella was the 2nd most commonly found microorganism noted in 11 (26.8%) cases. Conclusion: Frequency of UTI was high (31.5%) among asymptomatic jaundiced newborns. Children presenting with jaundice needs to be evaluated for UTI. Keywords: E.Coli, indirect hyperbilirubinemia, Klebsiella , Urinary tract infection (UTI).